Alterações renais em pacientes com doença falciforme - Silva Júnior, Geraldo Bezerra da (2013)
Background - Kidney abnormalities are one of the main chronic complications of sickle cell disease (SCD). The aim of this study is to investigate the occurrence of renal abnormalities among patients with SCD. Methods - This is a cohort study with 26 SCD patients followed in a medical center in Fortaleza, Ceará, Brazil. Urinary acidification and concentration tests were performed using calcium chloride (CaCl2), and after a 12h period of water and food deprivation. Fractional excretion of sodium (FENa), transtubular potassium gradient (TTKG) and solute free water reabsorption (TcH2O) were calculated. The SCD group was compared to a group of 15 healthy volunteers (control group). Aquaporin-2 (AQP2) and renal outer medullary K+ channels (ROMK) were quantified through exosomes search in urine. Results - Patient`s average age and gender were similar to controls. Urinary acidification deficit was found in 5 SCD patients (19.2%), who presented urinary pH > 5.5 after CaCl2 test. Urinary osmolality was significantly lower in SCD patients (355±60 vs. 818±202mOsm/kg, p=0.0001, after 12h period water deprivation). Urinary concentration deficit was found in all SCD patients (100%). FENa was higher among SCD patients (0.75±0.3 vs. 0.55±0.2%, p=0.02). The TTKG was higher in SCD patients (5.5±2.5 vs. 3.0±1.5, p=0.001), and TcH2O was lower (0.22±0.3 vs. 1.1±0.3L/day, p=0.0001). The search for AQP2 did not show significant difference between SCD patients and control group (102±6.0 vs. 100±7.2%, p=0.874), as well as for ROMK (172±38 vs. 100±25%, p=0.207). Conclusions - SCD is associated with important kidney dysfunction. The main abnormalities found were urinary concentrating and incomplete distal acidification defect. There was also an increase in the potassium transport and decrease in water transport, evidencing the occurrence of distal tubular dysfunction.